Lithostratigraphy of the Siwalik Group along the Muksar Khola section, Siraha-Udayapur District, Eastern Nepal Himalaya (Journal of Nepal Geological Society, 2020)
The Siwalik Group extending east to west co-linear to the main Himalayan range is well exposed along the Muksar Khola section, Siraha-Udayapur district, eastern Nepal Himalaya. Siwalik Group in the present study area is divided into the Lower, Middle, and Upper Siwaliks based on grain size and sandstone-mudstone proportion. The Lower Siwaliks is characterized by very fine- to fine-grained, light grey sandstone interbedded with dark grey to olive black mudstone. The Middle Siwaliks, is characterized by the domination of fine- to coarse-grained sandstone, and based on the lithology and bed thickness it is divided into two members. The lower member is dominated by fine- to medium-grained “salt and pepper” sandstone with dark greenish to olive-grey mudstone while, the upper member is dominated by light grey to white medium- to coarse-grained sandstone with grey, dark grey to black mudstone. Increase in the grain size and thickness of sandstone beds, increase in the proportion of mudstone, decrease in induration of sandstone and decrease in the proportion of biotite grain in sandstone makes upper member different from lower member of the Middle Siwaliks. The Upper Siwaliks is characterized by very thick beds of clast supported conglomerate associated with coarse- to very coarse-grained, very thick bedded sandstone and dull yellowish-grey to grey mudstone. The boundary between the Lower Siwaliks and the Middle Siwaliks, lower member and upper member of the Middle Siwaliks, and the Upper Siwaliks are 10.0 Ma, 5.7 Ma, and 3.5 Ma, respectively. The present study records the presence of a large succession of intra-formational conglomerate succession in the Lower Siwaliks.